PEMBELAJARAN BERDIFERENSIASI DALAM KERAGAMAN PESERTA DIDIK TERHADAP PEMENUHAN TARGET KURIKULUM - Arumsari, Asri; Susanti, Rahmi (Guruku: Jurnal Pendidikan Profesi Guru, 2023)
Differentiated learning is a form of effort in a series of learning that pays attention to the needs of students in terms of learning readiness, student learning profiles, interests and talents. So through differentiation learning carried out by educators it is hoped that they can achieve the target of fulfilling the independent curriculum, namely giving freedom to students of different religions to develop their talents and interests and produce a profile of Pancasila students who are targeted in this independent curriculum. In terms of differentiated learning, it can be in accordance with the philosophy of thought according to Ki Hajar Dewantara which states that education "guides" the nature of each student so that he is able to achieve the highest safety and happiness as a human being or a member in a society. In this case the educator acts as a facilitator who can provide direction so that the student does not lose his way and can become a complete human being.